Pimavanserin: A Novel Antipsychotic With Potentials to Address an Unmet Need of Older Adults With Dementia-Related Psychosis - Yunusa, Ismaeel; El Helou, Marie Line; Alsahali, Saud (Frontiers in Pharmacology, 2020)
Dementia affects more than 40 million people worldwide. When it is accompanied by psychosis, symptom management is especially challenging. Although no drug has been approved by the US Food and Drug Administration (FDA) for psychosis in patients with dementia, atypical antipsychotics are commonly used off label for this indication. However, antipsychotic use in elderly patients with dementia-related psychosis is associated with adverse reactions including motor function disorders, cognitive impairment, cerebrovascular events, and increased risk of death. In 2017, due to positive results of a phase II clinical trial in patients with Alzheimer’s disease-related psychosis, the FDA granted breakthrough therapy designation to the new antipsychotic pimavanserin for the treatment of dementia-related psychosis. This article reviews the pharmacological activity, clinical efficacy and safety, and current off-label use of pimavanserin for psychosis.